GAMBARAN PENGETAHUAN PASIEN TENTANG BEKAM SUNNAH YANG BERKUNJUNG KE PELAYANAN KESEHATAN KOMPLEMENTER BENGKULU - Efrizal Novsawindi (Universitas Bengkulu, 2022)
AbstrackCupping is a treatment prescribed by Allah SWT through the Prophet Muhammad, cupping therapy is a treatment by removing harmful dirty blood from the body by injuring the skin surface and then sucking it with a tool, cupping is highly recommended on 17, 19 and 21 Hijriyah. This study aims to determine the description of patient knowledge about Sunnah Cupping. The population of this study were all patients who visited the Bengkulu Complementary Health Service. The research method uses descriptive quantitative approach and sampling technique by accidental sampling obtained as many as 67 samples. The measuring instrument in this study used a questionnaire. The results of this study showed as many as 28 respondents (41.80%) with good category knowledge, 36 respondents (53.73%) with sufficient category knowledge and 3 respondents (4.47%) with poor category knowledge. Thus it can be concluded that based on the results of research on